2020
DOI: 10.3390/membranes10120431
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Optimization of the Graft Density of Functionalized Anti-Biofouling Surfaces by Cationic Brushes

Abstract: Diseases and complications related to catheter materials are severe problems in biomedical material applications, increasing the infection risk and medical expenses. Therefore, there is an enormous demand for catheter materials with antibacterial and antifouling properties. Considering this, in this work, we developed an approach of constructing antibacterial surfaces on polyurethane (PU) via surface-initiated atom transfer radical polymerization (SI-ATRP). A variety of cationic polymers were grafted on PU. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Most studies on the surface of particles have shown that the charge influences the ability to pass through membranes. The Zeta potential values of PU-based materials are found in a large range (between −20 and +30 mV) according to Y. Ren et al [73]; the positive values observed in the current samples can be related to the absence of free hydroxyl and carboxyl groups and to the presence of THAM as a crosslinker.…”
Section: Discussionmentioning
confidence: 60%
“…Most studies on the surface of particles have shown that the charge influences the ability to pass through membranes. The Zeta potential values of PU-based materials are found in a large range (between −20 and +30 mV) according to Y. Ren et al [73]; the positive values observed in the current samples can be related to the absence of free hydroxyl and carboxyl groups and to the presence of THAM as a crosslinker.…”
Section: Discussionmentioning
confidence: 60%
“…Ren et al grafted QACs onto a polyurethane (PU) surface via surface-initiated atom transfer radical polymerization (SI-ATRP), and then grafted PVP hydrogel onto the surface by a Fenton-like reaction. QACs could improve the hydrophilicity of PU, and the surface water contact angle decreased from 93.6 • to 60 • , inhibiting bacterial adhesion and killing bacteria [97].…”
Section: X For Peer Reviewmentioning
confidence: 99%
“…As curcuminoid molecules are functionalized, the surface charge increases due to the structure of the curcuminoids. These compounds contain nitrogen atoms in their structure, which can be protonated to enhance the surface charge [ 44 , 45 ]. These results align with the observed hydrodynamic diameters.…”
Section: Resultsmentioning
confidence: 99%